2016
DOI: 10.1093/nar/gkw720
|View full text |Cite
|
Sign up to set email alerts
|

Incision of damaged DNA in the presence of an impaired Smc5/6 complex imperils genome stability

Abstract: The Smc5/6 complex is implicated in homologous recombination-mediated DNA repair during DNA damage or replication stress. Here, we analysed genome-wide replication dynamics in a hypomorphic budding yeast mutant, smc6-P4. The overall replication dynamics in the smc6 mutant is similar to that in the wild-type cells. However, we captured a difference in the replication profile of an early S phase sample in the mutant, prompting the hypothesis that the mutant incorporates ribonucleotides and/or accumulates single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…If Sld2 or Sld3 depletion reduces the number of active origins per cell, then each active fork should be able to traverse a greater distance before running out of dNTPs [64]. We are able to measure how far these forks travel by mapping the positions of the ssDNA associated with active replication forks via in vitro labeling of nascent single-stranded regions with fluorescent nucleotides followed by hybridization to microarrays [50, 65, 66]. Active origins are revealed as peaks of ssDNA (Figs 5 and S8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If Sld2 or Sld3 depletion reduces the number of active origins per cell, then each active fork should be able to traverse a greater distance before running out of dNTPs [64]. We are able to measure how far these forks travel by mapping the positions of the ssDNA associated with active replication forks via in vitro labeling of nascent single-stranded regions with fluorescent nucleotides followed by hybridization to microarrays [50, 65, 66]. Active origins are revealed as peaks of ssDNA (Figs 5 and S8).…”
Section: Resultsmentioning
confidence: 99%
“…For a more comprehensive view of the behavior of origins under these conditions, we first defined origins as those producing clearly resolved peaks in the 30 min sample of wild type (W303) cells (red circles in S8 Fig and orange triangles in, Figs 5C and S9). Under the conservative criteria we used, we defined 117 origins (Materials and Methods), comparable to the 113 origins originally defined by the ssDNA assay [66]. We based our subsequent analyses of other samples using this set of 117 origins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis suggested that rDNA repeats, containing tens to hundreds of replication-fork-pausing sites (RPS), are the most prone to fork regression (particularly after inactivation of SMC5/6 [108]) and that reducing fork pausing (similar to mph1 deletion) improves rDNA replication in cells without SMC5/6. At highly transcribed rDNA, the RNA–DNA hybrids can block RF progression, and Mph1 must be controlled by SMC5/6 to avoid toxic RF regression [109,110]. In contrast to STR helicase, Mph1 regulation does not seem to be SUMO-dependent, suggesting a sole mechanistic restriction posed by the SMC5/6 complex (Figure 3c) [102,106].…”
Section: Smc5/6 Roles In Maintenance Of Genome Integritymentioning
confidence: 99%
“…The Smc5/6 complex plays an important role in mitotic proliferation as well as meiosis, and in maintenance of chromosome stability [10][11][12]. It is involved in rescue of collapsed replication forks [13,14], progression of replication forks [15,16] DNA double strand break repair and resolution of recombination intermediates [17,18]. The Smc5/6 complex in eukaryotic cells such as yeast has eight subunits that include Smc5, Smc6, and six non-Smc subunits (Non Smc Elements or Nse1-6), all of which are essential for viability.…”
Section: Introductionmentioning
confidence: 99%